Ficus deltoidea: Review on background and recent pharmacological potential - Mohammad Moneruzzaman, Khandaker; Amru Nasrulhaq, Boyce; J., Rosnah (Asian Network for Scientific Information, 2015)
Ficus deltoidea is a native plant of Malaysia which is very potential plant for varied purposes. It has diversed morphology and was spread throughout Malaysia and adjacent countries. Its great potential had been valued by the old folks and now it is getting famous as more attention given in exploring herbs as an alternative for medicine. Ficus deltoidea is an ultimate source of antioxidant and natural products. It is commercialized as tea and is proposed as a possible supplement for type II diabetes patients. Ficus deltoidea studied for its numerous pharmacological properties such as antioxidant and antidiabetic properties, anti-inflammation and antinociceptive activity, wound healing activity, antiulcerogenic effect, antibacterial, anticancer and also it’s potential as an uterotonic agent. This article review provide more thorough information about F. deltoidea plants in detail in term of plant, origin, morphology, ecology, variety, commercial usage and its pharmacological benefits.